Histological study on the fibrous architectecture of the adrenal gland during prenatal development in buffalo - SETHI, R S; ROY, K S; SINGH, OPINDER (The Indian Journal of Animal Sciences, 2011)
The study was conducted on the adrenal glands of 43 buffalo foetuses ranging from 39 mm to 890 mm crown rump length (CRL). Very few and fine collagen fibres and reticular fibres were observed in the peripheral areas of the adrenal primordia and aggregates of neuroectodermal tissue by 109 mm CRL stage. The glands were fully encapsulated in the fibrous tissue, predominantly made up of collagen fibres by 210 mm CRL stage. The connective tissue trabeculae made up of collagen and reticular fibres arose from the inner aspect of the capsule by 250 mm CRL stage. The trabeculae pierced cortical parenchyma of the gland to reach the medulla along with the medium sized blood vessels and nerve fibres. The inner aspect of the capsule had higher proportion of reticular fibres that entered into cortical and medullary tissue and arranged the parenchyma into follicular form in 470 mm CRL and onward stages. The definite cortex and outer zone of medulla had a higher proportion of reticular fibres. The capsule became fibromuscular had high proportion of collagen fibres intermingled with the reticular fibres, smooth muscle cells and a good number of blood vessels and nerve fibres. The elastic fibres were not observed in any part of the gland up to 890 mm CRL stages, however, they were present in the wall of blood vessels and perivascular tissue. Â